New system for stage determination of the structural changes in primary open-angle glaucoma based on morphometric analysis of the optic disk performed by Heidelberg Retina Tomograph II (version 3.1.2) - B. Anguelov; A. Toshev (Oftalʹmologiâ)
Purpose: To determine the correlation between global and sectoral topographic parameters (TP) of the optic nerve head (ONH) and the standard automated perimetry common indices, to assessment of the diagnostic accuracy of the ONH TPs in primary open-angle glaucoma (POAG) discrimination; to establish a combined staging system of glaucomatous structural damage based on global and sectoral TPs of ONH obtained by Heidelberg Retina Tomograph (HRT) II.Patientsand methods: 257 eyes of 176 patients (mean age 64±11), 69 (79 eyes) men and 107 (178 eyes) women were examined. They were separated in four groups: a control group of healthy volunteers and three groups of POAG patients with different severity of their visual field changes according to the Hodapp-Parrish-Anderson classification. Comprehensive ophthalmic examination, standard automated perimetry (SITA standard 30‑2) and examination with HRT II (3.1.2) were performed. Results: The TPs rim area (r = 0.469, r = –0.384) and rim volume (r = 0.431, r = –0.363) were most strongly correlated with the visual field changes expressed by the common indices — MD and PSD. The ONH TPs with highest diagnostic value were: cup shape measure (AUROC = 0.778), vertical cup / disc ratio (AUROC = 0.721), rim / disc area ratio (AUROC = 0.714), rim area (AUROC = 0.711) and rim volume (AUROC = 0.706). The staging system of glaucomatous structural damage based on global and sectoral TPs of ONH obtained by HRT II was established. It consists of four different stages: early, developed, advanced and terminal. Each of them is characterized by the interval of the chosen TP values.Conclusion: The changes of TPs rim area and rim volume determine the highest level of visual field changes in POAG. Cup shape measure is the most important TP in early glaucoma diagnostics. The proposed combined glaucoma staging system presents both the degree and the localization of the ONH defects together with some disease progression risk factors. The presence of standardized criteria allows its use in glaucoma progression follow-up.